Linkages between socioeconomic inequalities, pro-environmental behaviours, climate change concerns and experiences, and wellbeing outcomes in England - Jonathan R. Olsen; Claire L. Niedzwiedz; Ruth Dundas; Jala Rizeq; Gergő Baranyi; Srinivasa Vittal Katikireddi; Jill Pell (Sustainable Environment)
The global health community recognises climate change as a public health emergency due to its direct and indirect impacts on health and wellbeing. This study explores sociodemographic differences in climate change concern and pro-environmental behaviours by socioeconomic status, their association with wellbeing, and whether experiences of climate change (e.g. residing in flood-affected or temperature-changing areas) mediate wellbeing outcomes. Using data from Understanding Society, a national panel survey in England (2018/19, n = 24,950, age 16+), the study examined climate concern, 11 pro-environmental behaviours, satisfaction with these behaviours, and three wellbeing outcomes: life satisfaction, optimism, and psychological distress. Data were spatially linked with flood (2010–18) and summer temperature changes (2001–2020). Climate concern varied by sociodemographic factors, with older and disadvantaged groups most satisfied with their behaviours. Individuals satisfied with their environmental actions reported better wellbeing, while dissatisfaction was linked to distress and worse life satisfaction. However, pro-environmental behaviours themselves were not associated with wellbeing. Residing in flood-affected or temperature-changing areas also showed no link to wellbeing. Addressing wellbeing impacts related to climate concern requires targeted mitigation strategies, especially for those dissatisfied with their environmental actions. Pro-environmental behaviours could act to mitigate against the potential adverse effects of eco-anxiety.